Pengaruh Kualitas Produk, Motivasi dan Sikap Konsumen Terhadap Keputusan Pembelian Generasi Milenial Pengguna Marketplace Lazada - Putri Novita Sari; intisarih Haryanti (Indonesian Journal of Multidisciplinary on Social and Technology, 2024)
This study aims to determine the effect of product quality, motivation and consumer attitudes on purchasing decisions of the millennial generation on the Lazada marketplace, where this study uses causal associative research to look for the influence of product quality (X1) motivation (X2) consumer attitudes (X3) and purchase decisions (Y) with an unknown population size and uses a purposive sampling technique. sampling for data collection as many as 96 respondents. The research instrument uses a Likert scale using validity test, reliability test, classic assumption test, multiple linear regression, correlation coefficient analysis (R), coefficient of determination analysis (R2), t test and f test. The results showed that 1) there was a partial effect of product quality on purchasing decisions of the Lazada marketplace millennial generation with a t-count value of 2.6141, 2) there was a partial influence of motivation on purchasing decisions for the Lazada marketplace millennial generation with a t-count value of 3.209, 3) there was a partial influence on consumer attitudes towards purchasing decisions of the Lazada marketplace millennial generation with a t-count value of 5.309, 4) there was a simultaneous influence on product quality, motivation and consumer attitudes the buying decision of the millennial generation on the lazada marketplace obtained a calculated f value of 117.308.